Nitrogen management can boost rice (Oryza sativa L.) production near aluminium smelter: A field study - Panda, N; Dash, AK (ORYZA-An International Journal of Rice, 2021)
Nitrogen (N) management is a key to sustain rice yield under submerged condition. Time and amount of N application boost rice production under adverse environmental situation. To test this hypothesis a field experiment was conducted at different villages in and around Hindustan Aluminium Company Ltd. (HINDALCO), Hirakud, Sambalpur, Odisha in the year 2015 and 2016. The rice ecosystems were selected on the basis of distance from the smelter plant. Different treatments were framed to test the hypothesis as T1-Farmers practice (60:30:30 kg N: P2 O5:K2OÂ  ha-1); T2- 75% recommended dose of fertilizer (RDF) of nitrogen(N) ; T3 -100% RDF of N; T4 -125% RDF of N;Â  T5 -150% RDF of N. It was conducted in a randomized block design with four replications in the farmer's field. The test crop was rice cv.Tejaswinee. Growth parameters like plant height (cm), panicle length (cm) and number of effective tillers per hill were found to be highest in the plots where 125% RDF of N was applied. However the chlorophyll content(mg g-1 fresh)was estimated highest with 150 % RDF of N applied plots. The grain and straw yield (q ha-1) of rice were also observed highest with treatments receiving125% RDF of N.The rice ecosystems which are nearer to aluminium smelter plant were supposed to be affected with less yield as compared to far distance rice ecosystems. The grain quality parameterof rice like protein content (%) was also affected at smelter sites as compared to far distances. However with increasing the N level to 125 % RDF protein content was increased.